ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI PETANI DALAM MENINGKATKAN PRODUKSI PADI DI DESA BUNGARAYA KECAMATAN BUNGARAYA KABUPATEN SIAK - Zainal Arifin; Cepriadi '; Didi Muwardi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aimed to analyze the factors that influence the motivation of farmers and where the most dominant factor influencing motivation of farmers to increase rice production in the Village Bungaraya Subdistrict Bungaraya Siak. The analytical methods research used in the study is descriptive and using a scale likert the result showed that the factors that influence motivation of farmers to increase rice production is age, long time experience farming, long been a member of a group farmers, extension intensity, targeted instructor, the amount of resources, affordability production facilities, availability of production facilities, self-esteem, personal expectation, desires, needs, job satisfaction, the type and nature of work, the working group in which a person joins, the environmental situation in general, organizations where work, and reward system that apply. while the most dominant factor influencing motivation rice farmers are long experience of farming, long been a member of a group farmers, self-esteem and the environmental situation in general. Keywords: Motivation of farmers, Rice plants, Scale Likerts .